A critical study on the licensing system in Malaysia to combat illegal moneylending / Azian Adznan ...[et al.] - Adznan, Azian; Aminuddin, Herni Laily; Mohd Asri, Izzati; Ku Yosof, Ku Mohd Amir Aizat (2010)
The objective of this research is to analyse on how the law on licensing moneylending activities works by comparing Malaysian law to the law in the United Kingdom and Singapore. The number of illegal moneylender's problem keeps rising. This indicates that there must be something wrong with the law. This project paper shall cover Malaysia Moneylenders Act 1951 as amended in 2003, the Singapore Moneylenders Act 2008 Singapore and Consumer Credit Act 2006 of the United Kingdom. In this research, qualitative research methodology was utilized in this study, where two in-depth interviews have been conducted with the Ministry of Housing and Local Development and the other one with Malaysian Licensing Moneylenders Association (MILMA). The interviews show that the Singapore Moneylenders Act 2008 and the UK Consumer Credit Act 2008 is better than Malaysian Moneylenders Act 1951 as amended in 2003 does not cover all aspects regarding moneylending activities. In this research, for the issue of Ah Longs, it is limited only to issue of licensing rather than other aspects. This is important to make sure that issues that we are focusing for will be discuss in detail. The purpose is to see how the law on licensing in Malaysia relates to the issue of loan sharks.